GENDER OPPRESSION IN POST COLONIAL FICTION: HAMID’S PORTRAYAL OF WOMEN - Saba Hassan; Dr. Abdul Hamid Khan; Dr. Bilal Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
This study is about the gender oppression in Pakistani-English literature, focusing on the analysis of the selected novel through post-colonial feminism. The main aim of the researcher is to highlight how female gender has been represented by Mohsin Hamid. The study is an analysis to the representation of gender, analyzing how the writer has addressed feminist issues in his novel. The women marginalization and their lack of voice in the patriarchal society of Pakistan exist since British colonization. The present study focuses on Hamid’s portrayal of women. The novel represents an effort to challenge the double colonization of female gender, where females are subjugated by both the colonization as well as by patriarchal power in the Pakistani society. The researcher has selected Moth Smoke by Mohsin Hamid in terms of women's representation and gender oppression. The research is qualitative in nature where the researcher has analyzed the text of the novel through textual analysis technique. The result shows that woman as portrayed in the novel has been subjugated by the male counterpart in the patriarchal society and they do not have any voice against this oppression. Moreover, the writer has shown that the patriarchal powers have oppressed the female gender through many ways in the novel. Thus, gender issues persist in the writer’s novel.